Cascaded sliding mode position control (SMC-PI) for an improved dynamic behavior of elastic feed drives. (October 2021) - Neubauer, Michael; Brenner, Felix; Hinze, Christoph; Verl, Alexander
Abstract: The precision of machine tools is essentially determined by the feed drive control. To improve the dynamic behavior of elastic feed drives, this paper presents a novel position control concept, substituting the conventional P position controller of the industrial cascade control with a continuous sliding mode controller (SMC) together with a Kalman Filter for state estimation. The novelty of this approach lies in the focus on practical applicability: The underlying PI-cascade structure leads to low commissioning effort and the SMC controller's parameterization is simplified to a single tuning parameter. A general compliant feed drive model is used as plant, whose parameters usually are already known from commissioning of the velocity controller. The SMC position controller is derived analytically and its stability and damping properties are investigated for the dominating mechanical mode for uncertainties of the model parameters and a wide range of controller gains. The effectiveness of the SMC-PI controller is validated for an industrial ball screw feed drive. Extensive experimental results show a considerable decrease of tracking errors in command tracking, disturbance rejection and for a high speed cutting (HSC) milling experiment compared to P-PI cascade control, while stability margins remain almost independent of the controller gains. The parameterization is discussed on the basis of a theoretical analysis and measuring results. Furthermore, excellent robustness properties regarding model errors are demonstrated. Graphical abstract: Highlights: A sliding mode controller is applied as position controller for compliant mechanics. The higher-order controller is narrowed down to one gain, comparable to P control. Improvements in tracking and disturbance response compared to P-PI control. The controller is well-suited for HSC, which is shown experimentally. The robustness against errors in the model parameters of the controller is examined.